Natural Sources Screening for Antimicrobial Agent of Herbs, Spices, and Extracts: A Semi-Qualitative Study - Felix Arie Setiawan; Meta Fitri Rizkiana; Bekti Palupi; Istiqomah Rahmawati (University of Jember, 2020)
Indonesia has been recognized for its rich natural ingredients such as spices,herbs, and extracts for decades. Furthermore, these components also have been used as an herbal medicine for a long time. Meanwhile, the apparent capability comparison of several components of antimicrobial activity has not been updated yet. This study was conducting the comparison of antimicrobial activity for several materials such as noni (Morinda citrifolia), garlic (Allium sativum), celery (Apium graveolens), galangal (Alpinia galangal), ginger (Zingiber officinale), yellow turmeric (Curcuma longa), lime (Citrus aurantifolia), papaya (Carica papaya) leaf, betel (Piper betel) leaf, and cutcherry (Kaempferia galangal) using agar dilution method. Two types of bacteria are used for the test, namely gram-negative bacteria and gram-positive bacteria, with a total of seven bacteria. The media used were TSA (Trypticase Soy Agar) media for gram-negative bacteria and MRSA (Methicillin-Resistant Staphylococcus Aureus) media for gram-positive bacteria. This study had been conducted by using a fast screening method, which is referred to as a semi-qualitative method. Several components, such as noni, lime, and betel leaf, showed a significant result of antimicrobial activity. Otherwise, other compounds, surprisingly, could not suppress bacterial growth.